High proportion of abnormal pap smear tests and cervical dysplasia in women with cystic fibrosis. (February 2018) - Rousset-Jablonski, Christine; Reynaud, Quitterie; Nove-Josserand, Raphaëlle; Ray-Coquard, Isabelle; Mekki, Yahia; Golfier, François; Durieu, Isabelle; ,
Abstract: Objectives: Insufficient gynecological follow-up and cervical screening has been reported in women with cystic fibrosis (CF). Some of these patients will require a pulmonary transplantation, known to be associated with a higher risk of cervical dysplasia. The aim of this study was to explore the results of cervical screening in adult women with CF, and to report the prevalence of abnormal pap smear tests in this population. Study design: We retrospectively analyzed medical records of sexually active women with CF who attended a gynecological consultation in Lyon University CF referral center between June 2014 and December 2015. The primary outcome was the result of the pap smear test. Results: Forty-seven women (32 non-transplanted and 15 transplanted) were included in the study. The median age of the patients was 28 (range 18–53). The clinical examination revealed that 20 (42.5%) women presented an abnormality (inflammatory cervix, cervical or vulvovaginal condyloma). An abnormal pap smear was found in 8/32 (25%) non transplanted women and in 5/15 (33.3%) transplanted women, with no significant difference between the two groups (p = 0.75): seven atypical squamous cells of undetermined significance (ASC-US), five low grade squamous intraepithelial lesion (LSIL), one atypical glandular cells (AGC). Six (12.8%) (four non transplanted, and two transplanted) women had an histologically proven dysplasia (four Cervical Intraepithelial Neoplasia (CIN)1, one CIN2, and one endocervical adenocarcinoma in situ ). Overall, ten (21.3%) women had a Human Papilloma Virus (HPV) related disease (cervical and/or vulvovaginal). Conclusion: A high proportion of transplanted and non-transplanted women with CF had abnormal pap smear tests and cervical dysplasia. A regular gynaecological follow-up, periodic cervical screening, and routine HPV vaccination are strongly recommended in this population.